Low Velocity-Ratio Pitched and Skewed Jet in a Turbulent Boundary Layer - Jewkes, James; Chung, Y. (University of Auckland, 2010)
The jet in cross-flow (JICF) is a commonly studied flow in the context of boundary layer control. Particularly, pitched and skewed jets has potential for flow separation control. In this study, both the perpendicular and the pitched and skewed jets were considered to highlight the different flow structures. The formation of the vortical ‘shell’ was clearly seen in a low velocity-ratio perpendicular JICF, while no such structure was observed in the pitched and skewed case. Instantaneous and time-averaged flow field were analysed in this paper.